(untitled) (Itinera, 2025)
The article discusses Foucault’s «technologies of the self» by reconsidering the link between ethics and aesthetics in this paradigm, with a view to its possible application to selfie technology as a «gestural image» (Frosh). This reconsideration stems from a close examination of the self as understood by the concept of technologies of the self, emphasizing also the aesthetic aspects of its rationality and of its phenomenological dimension. The article also highlights how technologies of the self fail to overturn the logic of domination, which is still present in Foucault’s formulation and is likewise evident in «performative» interpretations of both Foucault’s technologies of the self and of the techno-social phenomenon of the selfie. From this perspective, the article proposes not to consider the «self of the selfie» as a mere support for self-narrative or as a product of performative action, but rather to view it as a «low-resolution self». In displaying itself through an act of outward projection within often complex situations and environments, this «low-resolution self» embodies a new ethos of coexistence and connectivity. On this basis, the question of interpreting the selfie phenomenon as a technology of the self shifts into a broader inquiry, where the focus moves from a technology of the self to an ecology of the self.